In vivo and in vitro evaluation of octyl methoxycinnamate liposomes - de Carvalho Varjão Mota A; Freitas ZMF; Ricci Júnior E; Dellamora-Ortiz GM; Santos-Oliveira R; Ozzetti RA; Vergnanini AL; Lira Ribeiro V; Silva RS; Santos EP (International Journal of Nanomedicine, 2013)
Aline de Carvalho Varjão Mota,1 Zaida Maria Faria de Freitas,1 Eduardo Ricci Júnior,1 Gisela Maria Dellamora-Ortiz,1 Ralph Santos-Oliveira,2 Rafael Antonio Ozzetti,3 André Luiz Vergnanini,3 Vanessa Lira Ribeiro,4 Ronald Santos Silva,4 Elisabete Pereira dos Santos11Faculty of Pharmacy, Federal University of Rio de Janeiro, 2Nuclear Engineering Institute, National Nuclear Energy Commission, 3Allergisa Dermatocosmetic Research, University of Campinas, São Paulo, 4Pharmacology and Toxicology Department, National Insitute of Quality Control in Health, Oswaldo Cruz Foundation, Rio de Janeiro, BrazilAbstract: Solar radiation causes damage to human skin, and photoprotection is the main way to prevent these harmful effects. The development of sunscreen formulations containing nanosystems is of great interest in the pharmaceutical and cosmetic industries because of the many potential benefits. This study aimed to develop and evaluate an octyl methoxycinnamate (OMC) liposomal nanosystem (liposome/OMC) to obtain a sunscreen formulation with improved safety and efficacy by retaining OMC for longer on the stratum corneum.Methods: The liposome/OMC nanostructure obtained was tested for enzymatic hydrolysis with lipase from Rhizomucor miehei and biodistribution with liposomes labeled with technetium-99m. The liposome/OMC formulation was then incorporated in a gel formulation and tested for ocular irritation using the hen’s egg test-chorio-allantoic membrane (HET-CAM) assay, in vitro and in vivo sun protection factor, in vitro release profile, skin biometrics, and in vivo tape stripping.Results: The liposome/OMC nanosystem was not hydrolyzed from R. miehei by lipase. In the biodistribution assay, the liposome/OMC formulation labeled with technetium-99m had mainly deposited in the skin, while for OMC the main organ was the liver, showing that the liposome had higher affinity for the skin than OMC. The liposome/OMC formulation was classified as nonirritating in the HET-CAM test, indicating good histocompatibility. The formulation containing liposome/OMC had a higher in vivo solar photoprotection factor, but did not show increased water resistance. Inclusion in liposomes was able to slow down the release of OMC from the formulation, with a lower steady-state flux (3.9 ± 0.33 µg/cm2/hour) compared with the conventional formulation (6.3 ± 1.21 µg/cm2/hour). The stripping method showed increased uptake of OMC in the stratum corneum, giving an amount of 22.64 ± 7.55 µg/cm2 of OMC, which was higher than the amount found for the conventional formulation (14.57 ± 2.30 µg/cm2).Conclusion: These results indicate that liposomes are superior carriers for OMC, and confer greater safety and efficacy to sunscreen formulations.Keywords: sunscreen, liposome, tape stripping, technetium-99-m, lipase